Application of a Stereoselective Rhodium(II)-Catalyzed Oxonium Ylide Formation–[2,3]-Sigmatropic Rearrangement of an α-Diazo-β-keto Ester to the Synthesis of 2-epi-Cinatrin C1 Dimethyl Ester - Yakura, Takayuki; Ozono, Ayaka; Matsui, Katsuaki; Yamashita, Masayuki; Fujiwara, Tomoya (Synlett, 2013)
The Rh2(OAc)4-catalyzed oxonium ylide formation–[2,3]-sigmatropic rearrangement of a highly functionalized α-diazo-β-keto ester derived from d-glucose proceeded stereoselectively to give the corresponding tetrahydrofuran-3-one as a single diastereomer in high yield. This reaction was applied to the synthesis of 2-epi-cinatrin C1 dimethyl ester as a key step.
Keywords: diazoketo ester; rhodium(II) catalyst; oxonium ylide; [2,3]-sigmatropic rearrangement; cinatrin